Local Wisdom and Oral History in Education: Storytelling as a Bridge for Cultural Sustainabilit - Hasmiza Hasmiza; Lia Khalisa; Adam Idris; Sitti Agustina (International Journal of Educational Narratives, 2025)
Background. The erosion of local wisdom and oral traditions in modern education threatens cultural continuity and identity among younger generations. The study explores storytelling as a pedagogical bridge to sustain cultural values through education. Purpose. The research aims to examine how oral history and indigenous narratives can be integrated into formal learning to promote cultural awareness, moral development, and intergenerational connection. Method. Using a qualitative descriptive design, the study employed interviews, classroom observations, and content analysis in selected elementary schools in Central Java and Bali. Teachers, students, and community elders were involved as participants to document and interpret local narratives used in classroom instruction. Results. The findings reveal that storytelling serves as a dynamic learning medium that enhances students’ empathy, creativity, and understanding of local identity. The integration of oral history into the curriculum also strengthens social cohesion by positioning traditional knowledge as a living source of moral and environmental education. Conclusion. The research concludes that incorporating local narratives within pedagogical frameworks revitalizes indigenous wisdom while enriching 21st-century education. The study recommends teacher training and curriculum reform emphasizing community-based storytelling as a tool for sustainable cultural education.